Pengoptimalan dosis dan waktu papar aplikasi sulfuril fluorida pada ketebalan kayu berbeda untuk pengendalian rayap kayu kering - Alfian, Ahmad Mansuri; Harahap, Idham Sakti; Priyambodo, Swastiko (Jurnal Entomologi Indonesia, 2016)
Termite, is one of the most damaging pest for wood product. One of the common fumigant use to control termite is sulfuryl fluoride. The objective of this study were to determine the dose-exposure and time for sulfuryl fluoride to kill dry wood termite Cryptotermes cynocephalus Kemner and evaluate the ability of fumigant to penetrate a rubber wood block. Application and penetration of the fumigant was tested on a 10 cm depth wood block, and conducted with 5 varied doses (10−30 g/m3) and 4 varied exposure time (6−24 hours). Application of the fumigant were tested on an 5 and 2.5 cm depth wood block. Doses were applied using 4 (four) different doses (2−15 g/m3) and 4 varied exposure time (1−9 hours). The study was conducted using randomize completely design with factorials. Results showed the application of sulfuryl fluoride was effective in penetrate 10 cm depth of wood block. The dose that was effective was of 30 g/m3 with 18 hours exposure time or a dose of 15 g/m3 with 24 hours exposure time. Application of depth penetration of 5 cm effectively done by using a dose of 10 g/m3 with 9 hours exposure and depth penetration of 2.5 cm using a dose of 15 g/m3 with 6 hours exposure time. Dose-time relationship for application of sulfuryl fluoride to penetrate of 10 cm showed dose variable is a slightly more important than exposure time, while to penetration of 5 and 2.5 cm showed exposure time variable is a slightly more important than dose of fumigant.